The Internationalization and Performance of SMEs: Growth Vs. Profitability - LU, Wenzhen, Jane (Institutional Knowledge at Singapore Management University, 2010)
Lu and Beamish (2001) examined the effect of two internationalization strategies, exporting and foreign direct investment (FDI), on SME performance (ROA). We extend this research by examining the differential effects of these strategies on two other dimensions of SME performance: growth and ROS. We develop and test four sets of hypotheses using a sample of 164 Japanese SMEs. We find that exporting activity has a positive impact on growth, but negative impact on profitability. FDI activity has a positive relationship with growth, but a U curve relationship with profitability. Exporting activity has a positive moderating effect on the relationship between an SMEÆs FDI activity and firm growth, a negative moderating effect on the relationship between an SMEÆs FDI activity and firm profitability. An SMEÆs age when it starts to make FDIs has a negative moderating impact on the relationship between FDI and firm growth and profitability.